Use of Procalcitonin to Guide Discontinuation of Antimicrobial Therapy in Patients with Persistent Intra-Abdominal Collections: A Case Series - Gabriel Motoa; Amy Pate; Carlos Franco-Paredes; Daniel B. Chastain; Andrés F. Henao-Martínez; Leila Hojat (Case Reports in Infectious Diseases)
Objective. Limited evidence exists for the use of procalcitonin (PCT) to guide the duration of antimicrobial therapy in patients with intra-abdominal abscesses (IAA). In this case series, we describe clinical presentations and outcomes using PCT to guide cessation of antimicrobial therapy in patients with persistent IAA who exhibited clinical improvement. Methods. A retrospective analysis of patients with IAA who had PCT levels available to review was performed in a tertiary academic teaching institution in the United States between 2017 and 2018. Demographics, clinical characteristics, and outcomes were obtained from the medical records. Patients were followed up for a minimum of 180 days after completion of antimicrobial therapy to determine if evidence of recurrence or mortality was present. Results. We identified four patients with IAA. They underwent early drainage of the source of infection and received empiric antimicrobial therapy according to individual risk factors and clinical scenarios. Antimicrobials were discontinued after clinical and radiographic improvement and evidence of normal PCT levels, regardless of the persistence of fluid collections. No evidence of recurrence or mortality was observed during the follow-up period. Conclusions. We found PCT to be a useful aid in the medical decision-making process to safely discontinue antimicrobial therapy in a series of patients with persistent intra-abdominal collections despite early drainage and appropriate course of antimicrobial therapy.